The Dead Sea Scrolls in Their Hellenistic Context - Hartog, Pieter B. (Dead Sea discoveries, 2017)
This introduction aims at situating the contributions of the Thematic Issue into wider debates on Hellenism and Hellenisation and changes taking place in scholarship. Essentialist notions of Hellenism are strongly rejected, but how then to study the Dead Sea Scrolls and the Qumran site during the Hellenistic period? Each contextualisation depends on the (comparative) material selected, and themes here vary from literary genres, textual practices, and forms of producing knowledge, to material culture, networks, and social organizations. All contributors see some embeddedness in ideas and practices attested elsewhere in the Hellenistic empires or taking place because of changes during the Hellenistic period. In this framework, similarities are overemphasized, but some differences are also suggested. Most importantly, the question of Hellenism is a question of relocating Jewish and Judaean evidence in the study of ancient history.